Recent developments in the management of pleural infection: a comprehensive review - Bedawi, E; Hassan, M; Rahman, N (Wiley, 2018)
Objectives: Pleural infection is a condition commonly encountered by the respiratory physician. This review aims to provide the reader with an update on the most recent data regarding the epidemiology, microbiology, and the management of pleural infection. Data source: Medline was searched for articles related to pleural infection using the terms “pleural infection,” “empyema,” and “parapneumonic.” The search was limited to the years 1997‐2017. Only human studies and reports in English were included. Results: A rise in the incidence of pleural infection is seen worldwide. Despite the improvement in healthcare practices, the mortality from pleural infection remains high. The role of oral microflora in the etiology of pleural infection is firmly established. A concise review of the recent insights on the pathogenesis of pleural infections is presented. A particular focus is made on the role of tPA, DNAse and similar substances and their interaction with inflammatory cells and how this affects the pathogenesis and treatment of pleural infection. Conclusion: Pleural infection is a common disease with significant morbidity and mortality, as well as a considerable economic burden. The role of medical management is expanding thanks to the widespread use of newer treatments.